2018
DOI: 10.1038/s41598-018-19243-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between modified CHA2DS2-VASc Score with Ankle-Brachial index < 0.9

Abstract: The ankle-brachial index (ABI) is a reliable diagnostic examination for peripheral arterial occlusive disease (PAOD). We previously reported CHADS 2 score was significantly correlated with PAOD. However, the association between CHA 2 DS 2 -VASc score and ABI < 0.9 is not evaluated in the literature. The aim of the present study was to investigate whether CHA 2 DS 2 -VASc score has a strong association with PAOD. We enrolled 1482 patients in this study. PAOD was defined as ABI < 0.9 in either leg. Vascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…However, data on PAD on this issue are limited in the literature. In the studies of Hsu et al [13][14][15] evaluated the association between Ankle-Brachial Index (ABI) and CHADS 2 and modified CHA 2 DS 2 -VASc scores. In the first study, they showed that the association between CHADS 2 score and ABI < 0.9 and confirmed CHADS 2 score was significantly associated with ABI < 0.9 in non-AF patients [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data on PAD on this issue are limited in the literature. In the studies of Hsu et al [13][14][15] evaluated the association between Ankle-Brachial Index (ABI) and CHADS 2 and modified CHA 2 DS 2 -VASc scores. In the first study, they showed that the association between CHADS 2 score and ABI < 0.9 and confirmed CHADS 2 score was significantly associated with ABI < 0.9 in non-AF patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…After than they demonstrated that CHADS 2 score was useful in predicting the risk of new-onset PAD [14]. In their last study determined that modified CHA 2 DS 2 -VASc score was significantly associated with ABI < 0.9 and they argued that calculation of modified CHA 2 DS 2 -VASc score may be beneficial in recognizing patients with PAD and in graduating the risk of PAD [15]. In our study, the results are consistent with the results in these studies and as well as these scores, ASCVD score model has been shown to be related to the PAD stage.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al reported that CHADS 2 score has good correlation with ankle-brachial index (ABI) <0.9 and it has good performance in predicting the risk of new onset PAD in patients without atrial fibrillation [10,11]. They also found that a modified CHA 2 DS 2 -VASc score, excluding peripheral arterial occlusive disease from the original vascular disease item, was significantly associated with ABI <0.9 [27]. In line with the studies by Hsu et al, we found that the risk of PAD was significantly increased with increasing CHADS 2 and CHA 2 DS 2 ASc scores in SA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Η παρατήρηση αυτή είναι σημαντική δεδομένου ότι και οι δύο δείκτες έχουν συσχετισθεί ανεξάρτητα με την πιθανότητα εκδήλωσης ΑΕΕ στους ασθενείς αυτούς. Τα αποτελέσματα αυτά έρχονται να προστεθούν στα ελάχιστα, μέχρι τώρα, και αντικρουόμενα δεδομένα που αφορούν στη σχέση αυτή(207)(208)(209)(210).Αφετέρου, για πρώτη φορά, τεκμηριώνει την ύπαρξη θετικής συσχέτισης μεταξύ του καρώτιδο -μηριαίου PWV και του CHA 2 DS 2 -VASc σκορ σε ασθενείς με ΚΜ.Στη διεθνή βιβλιογραφία υπάρχουν μικρές μελέτες που συγκρίνουν το CHA 2 DS 2 -VASc με διάφορες παραμέτρους της αγγειακής λειτουργίας, που με την ευρεία έννοια μπορούν να θεωρηθούν οτι αντικατοπτρίζουν την αρτηριακή σκληρία, και δείχνουν ότι ίσως υπάρχει θετική συσχέτιση των δύο μεγεθών(211)(212)(213). Η παρούσα μελέτη, όμως, απ' όσο γνωρίζουμε, είναι η πρώτη που εξετάζει τη σχέση του σκορ CHA 2 DS 2 -VASc με το PWV, το οποίο, όπως αναφέρθηκε, έχει συσχετιστεί σε μεγάλο αριθμό μελετών με την καρδιαγγειακή πρόγνωση.Δεδομένου οτι στον υπολογισμό του CHA 2 DS 2 -VASc δεν είναι όλοι οι παράγοντες ισότιμοι, η ανεύρεση συσχέτισης μεταξύ του σκορ (ανεξάρτητα από το ποιες επιμέρους συνιστώσες του υφίστανται σε κάθε ασθενή) και της αορτικής σκληρίας παρουσιάζει ιδιαίτερο ενδιαφέρον.Η συσχέτιση αυτή αξίζει να διερευνηθεί περαιτέρω προκειμένου να καθοριστεί η αξία του CHA 2 DS 2 -VASc στην πρόβλεψη της υψηλής αρτηριακής σκληρίας, τόσο σε ασθενείς με ΚΜ, όσο και στο γενικό πληθυσμό, ιδιαίτερα εφόσον ο υπολογισμός του σκορ αυτού είναι πολύ απλούστερος από τη μέτρηση της αρτηριακής σκληρίας.…”
unclassified